APPLYING NUTRIENTS IN COW ORGANISM AT DIFFERENT ENERGY SUPPLY - Kambur, M. D. (Scientific Progress & Innovations, 2019)
The article provides data on digesting and using nutrients in cow organism under the conditions of dif-ferent energy supply. The results of the conducted studies indicate that the balance of nitrogen was positive in animals of all groups. Animals of the first (control) group used 24.54 % of the consumed nitrogen and 30.24 % of digestible nitrogen. These indices were correspondingly: 28.58−35.59 % and 37.95−45.86 % in the second and third groups. The total amount of nitrogen used by cows was 264.86 g in the first group, which constituted 45.99% of the consumed and 56.53% of the digestible. In the second group, the figures were: 277.19 g, 49.82 % and 61.66 % correspondingly. The balance of calcium was characterized by a high level of using this element by cows of all groups during the second month of lactation. The animals of the control group altogether used 131.55 g of calcium, which constituted 69.45 % of the consumed and 99.62% of the digested calcium. The corresponding indices in the second and third groups of animals were: 124.63; 63.64; 99.59; and 151, 83; 69.59 and 92.719 %. A high level of using nutrients contributed to the fact that milk productivity of the control group of cows during the lactation period was: 4387.3 kg of genuine and 4168.4 kg of 4 % milk. On the average, 4484.6 kg of genuine milk and 4541.9 kg of 4 % milk was obtained from the cows of the second group. The annual yield of genuine milk from cows of the third group amounted to 5250.5 kg, and 5494.9 kg of 4 % milk, which was 1.20−1.32 times more than in the control group of cows (p<0.01). During six months of lactation, fat content of milk was higher in the experimental groups of cows. This indicator in the control group was 3.69 %, and 3.90 %, 3.97 % in the second and third groups of ani-mals, correspondingly. The data indicate that the lowest percentage of fat in milk was found at the highest daily yield. The percentage of fat in milk noticeably reduced to the fourth month of lactation, and then again increased till the seventh month of lactation. Such tendency was characteristic of all animal groups.